„Dawność w teraźniejszości”: Ewolucja polskich koncepcji pamięciowych od pierwszej połowy XX wieku do współczesności - Moskwa, Dagmara (Studia Polityczne, 2024)
In today’s globalized world of science and culture, the exchange of research ideas across national borders has become increasingly common and dynamic. However, not all theoretical frameworks receive equal attention beyond their country of origin—some remain largely overlooked, even by scholars in their own academic communities. This phenomenon can be clearly observed in the field of memory studies in Poland. This article is divided into two main sections. The first outlines key memory-related concepts developed by early Polish thinkers such as Ludwik Krzywicki, Kazimierz Kelles-Krauz, Florian Znaniecki, Józef Chałasiński, and Stefan Czarnowski, highlighting parallels with internationally recognized classical theories of memory. The second section reviews the contributions of contemporary Polish memory scholars after 2011, examining the extent to which they engage with both these earlier domestic theories and influential international approaches. Additionally, the article reflects on the current state of memory studies in Poland, including the prospects for the formation of memory studies as a distinct academic discipline.